POSSIBILITIES OF APPLYING THE COACHING METHOD IN THE TEACHERS’ CAREER - Rudžinskienė, Rasa (Acta Paedagogica Vilnensia, 2013)
Radical changes in the country affect a person’s social life. A person should be flexible, able to adapt to changes. Consequently, modern, innovatory methods allowing to develop the person’s inner potential are necessary in today’s society. The variety of the concepts of coaching, its mains principles, and the competence of a personal coach are analyzed in the article. The concept of coaching can be associated with the process of learning, self-education, assistance offering, and motivation stimulation. The popularity of coaching is rapidly increasing in Lithuania, but this method has not been widely analyzed. Also, the basic techniques of coaching and its interfaces with other sciences have been examined. A frequent problem of a teacher working in school is not applying the modern and innovative methods. The coaching in pedagogy pursues its aims through the strategies of progressive development and appliance of internal potential. These strategies are oriented to the result of creating and developing integral skills and abilities. The teacher’s approach to the opportunities of the coaching method application in pedagogy is also analyzed in the article. The results of the research show that the concept of coaching is not yet clear enough to teachers. In summary, the interest of coaching prevails; this method is estimated approvingly, but the information on practicing these techniques in pedagogy is lacking. Coaching can be described as a new form of learning. The main aim of this new form of learning is the mutual understanding between teachers and learners. Coaching can be named as a perfect instrument for the modern teacher and for the modern training process.